Metabolic remodeling of white adipose tissue in obesity - Cummins, Timothy D; Holden, Candice R; Sansbury, Brian E; Gibb, Andrew A; Shah, Jasmit; Zafar, Nagma; Tang, Yunan; Hellmann, Jason; Rai, Shesh N; Spite, Matthew; Bhatnagar, Aruni; Hill, Bradford G (American journal of physiology: endocrinology and metabolism, 2014)
Adipose tissue metabolism is a critical regulator of adiposity and whole body energy expenditure; however, metabolic changes that occur in white adipose tissue (WAT) with obesity remain unclear. The purpose of this study was to understand the metabolic and bioenergetic changes occurring in WAT with obesity. Wild-type (C57BL/6J) mice fed a high-fat diet (HFD) showed significant increases in whole body adiposity, had significantly lower V̇(O₂), V̇(CO₂), and respiratory exchange ratios, and demonstrated worsened glucose and insulin tolerance compared with low-fat-fed mice. Metabolomic analysis of WAT showed marked changes in lipid, amino acid, carbohydrate, nucleotide, and energy metabolism. Tissue levels of succinate and malate were elevated, and metabolites that could enter the Krebs cycle via anaplerosis were mostly diminished in high-fat-fed mice, suggesting altered mitochondrial metabolism. Despite no change in basal oxygen consumption or mitochondrial DNA abundance, citrate synthase activity was decreased by more than 50%, and responses to FCCP were increased in WAT from mice fed a high-fat diet. Moreover, Pgc1a was downregulated and Cox7a1 upregulated after 6 wk of HFD. After 12 wk of high-fat diet, the abundance of several proteins in the mitochondrial respiratory chain or matrix was diminished. These changes were accompanied by increased Parkin and Pink1, decreased p62 and LC3-I, and ultrastructural changes suggestive of autophagy and mitochondrial remodeling. These studies demonstrate coordinated restructuring of metabolism and autophagy that could contribute to the hypertrophy and whitening of adipose tissue in obesity.